2020
DOI: 10.1155/2020/7879436
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Performance of Daily Intake of a Homotaurine, Carnosine, Forskolin, Vitamin B2, Vitamin B6, and Magnesium Based Food Supplement for the Maintenance of Visual Function in Patients with Primary Open Angle Glaucoma

Abstract: Background. Glaucoma is a multifactorial optic neuropathy, which causes a continuous loss of retinal ganglion cells. Given the neurodegenerative nature of glaucoma, the necessity for neuroprotective intervention still arises, to be added alongside hypotonic therapy. Objective. The objective of this study was to assess the effect of daily intake of a homotaurine, carnosine, forskolin, vitamins B1, B2, and B6, folic acid, and magnesium based supplement (GANGLIOLIFE®) on the progression rates of the visual field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In POAG, it may act by preventing the aggregation and formation of amyloid plaques, also found at the level of RGCs, responsible for cell death [19]. Due to its affinity to GABA A receptors, it modulates cortical inhibitory activity by reducing the response of neurons to excitatory stimuli of glutamate [20,21], the pathogenic mechanism through which the RGCs and other nerve cells die as a consequence of an excess of extracellular glutamate [22].…”
Section: Introductionmentioning
confidence: 99%
“…In POAG, it may act by preventing the aggregation and formation of amyloid plaques, also found at the level of RGCs, responsible for cell death [19]. Due to its affinity to GABA A receptors, it modulates cortical inhibitory activity by reducing the response of neurons to excitatory stimuli of glutamate [20,21], the pathogenic mechanism through which the RGCs and other nerve cells die as a consequence of an excess of extracellular glutamate [22].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, supplementation with tablets containing C. forskohlii extract, homotaurine, carnosine, folic acid, vitamins of the B group and magnesium in POAG patients compensated by IOP-lowering drugs during a period of 12 months showed a significant further decrease in IOP and an improvement in the pattern electroretinogram amplitude at 6, 9 and 12 months, and foveal sensitivity at 12 months [266]. In another study, daily intake of a similar supplement for 4 months showed a decrease in IOP, improved light sensitivity and contrast sensitivity and a better quality of life in POAG patients [267]. Additionally, supplementation with French maritime pine bark/bilberry fruit extracts rich in anthocyanins to POAG patients for 4 weeks showed a reduced IOP [268].…”
Section: Challenges For Natural Product Application In Glaucoma Treatmentmentioning
confidence: 86%
“…Carnosine (N-b-alanyl-L-histidine), an effective antiviral, antioxidant and antiglycating agent, is a naturally occurring dipeptide [51][52][53][54][55]. It is present in skeletal system, cardiac muscles and brain of vertebrates [56,57].…”
Section: Carnosinementioning
confidence: 99%